An evidence‐based review of primary spontaneous pneumothorax in the adolescent population. Issue 3 (18th June 2021) - Wilson, Paria M.; Rymeski, Beth; Xu, Xuefeng; Hardie, William
Abstract: Primary spontaneous pneumothorax (PSP) is a relatively common problem in emergency medicine. The incidence of PSP peaks in adolescence and is most common in tall, thin males. Recent advances in the care of patients with PSP have called into question traditional approaches to management. This clinical review highlights the changing management strategies for PSP and concludes with a proposed evidence‐based pathway to guide the care of adolescents with PSP.